Emerging flexible sensor prototype - Chen, Ying (Nanyang Technological University, 2022)
Surface electromyography (EMG) and electrocardiogram (ECG) contain a large amount of information that characterizes the biological characteristics of muscles and the physiological state of the heart. They are both relatively weak bioelectrical signals and are easily disturbed by a variety of noises. This paper proposes a flexible sensor prototype circuit, which attaches disposable electrodes to the surface of human skin to collect EMG and ECG signals and amplifies the detected signals through the AD623 circuit. The MCP6001T -I/OT voltage divider bias amplifier provides the reference voltage for the AD623 circuit and converts the reference voltage of the amplified signal from 0V to 1.15V. Based on NRF52832, the measured signal is converted from analog to digital and sent to the host computer through Bluetooth 5.0, to realize the non-invasive acquisition, wireless transmission and real-time display of surface EMG signal. Experiments show that this acquisition method can detect obvious surface electromyogram (EMG) changes and surface electrocardiogram (ECG) signals, and successfully realize the transmission and reception of data between Bluetooth. Key words: EMG, ECG, flexible sensor prototype, AD623, MCP6001T - I/OT, NRF52832, Bluetooth